Baux’s and Abbreviated Burn Severity Score for the Prediction of Mortality in Patients with Acute Burn Injury - Dahal, Peeyush; Ghimire, Sanjita; Maharjan, Nirvana Kumar; Rai, Shakar Man (Journal of College of Medical Sciences-Nepal, 2016)
jdjd Background & Objectives: Prediction of outcome for patients with major thermal injury is important to inform clinical decision making, alleviate individual suffering and improve hospital resource allocation. Early prediction of outcome (i.e., survival or mortality) may help triage effectively, and to implement medical and surgical interventions efficiently as soon as possible. Burn mortality has decreased markedly with the improvement in burn management in the past 100 years, and multiple burn mortality prediction models have been developed over these times in response to that decline. But these services are still not enough to reduce the burn related injuries in low income country like Nepal. So we did a study to observe the effectiveness of two different but very popular models (Baux and ABSI) in our context. Materials & Methods: This was a prospective observational study where 92 cases of severe burn injury was selected and the results were compared with Baux and ABSI scoring system. Results: Total admission was 140 and mortality was 33. Out of these admission 92 cases of severe burn injury was selected for the study. Most (85.8 %) of were among the young group 16-40 years. It comprises 41.3 % in total. In total 63.7 % were female. Mortality with severe burn injury was 29.3%. No death had occurred below the Baux’s score 30 and there was more than 51% mortality above the score of 60. There was no mortality with ABSI scoring < 3 and mortality was high in ABSI scoring > 6. Conclusion: Baux and ABSI score systems are simple to calculate and ABSI is more accurate for prediction of acute burn injury. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 24-27